2022
DOI: 10.1186/s12873-022-00575-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of patients screened by rapid response team who transferred to the intensive care unit

Abstract: Background The utilization of a rapid response team (RRT) has influenced the clinical outcomes of patients in the general ward. However, the characteristics of RRT-screened patients who are transferred to the intensive care unit (ICU) are unknown. Therefore, the present study aimed to evaluate these factors. Methods We conducted a retrospective study using patient data from a tertiary medical center in Republic of Korea between January 2016 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
(60 reference statements)
0
6
3
Order By: Relevance
“…We found that ICU admission rates in this study were notably more varied compared to previous research [12,[16][17][18][19][20]. Jones et al documented that ICU admission rates through RRS activations uctuated between 10-25% [16],, yet other observational studies have observed even broader ranges, reaching up to 57% [12,[17][18][19][20][21].…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…We found that ICU admission rates in this study were notably more varied compared to previous research [12,[16][17][18][19][20]. Jones et al documented that ICU admission rates through RRS activations uctuated between 10-25% [16],, yet other observational studies have observed even broader ranges, reaching up to 57% [12,[17][18][19][20][21].…”
Section: Discussioncontrasting
confidence: 53%
“…When the Rapid Response System (RRS) is triggered for a ward patient, the RRS team must decide whether to escalate care to the ICU or continue management on the ward. While various exploratory studies have identi ed factors in uencing ICU admissions post-RRS activation [12][13][14], the external validity of these indicators remains unveri ed, and no standardized criteria for ICU admission have been universally adopted. Jones et al reported that decisions for ICU admission were in uenced by the sta ng levels and experience on the ward, the availability of ICU beds, and the feasibility of administering speci c treatments in both the ward and high-dependency settings [15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“….40] vs. 9.60 [6.40-14.0] 10 3 /µL, P < 0.001), and lactate level (2.40 [1.40-4.50] vs. 1.70 [1.16-2.88] mEq/L, P < 0.001) were higher in the ICU group than in the GW group. In addition, patients admitted to the ICU had a longer hospitalization time prior to RRT activation than those who were not (6 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] vs. 4 [1][2] days; P < 0.001). There were no signi cant between-group differences in terms of other characteristics (…”
Section: Patients' Baseline Characteristicsmentioning
confidence: 99%